Social Integration and Health Among Young Migrants in China: Mediated by Social Mentality and Moderated by Gender - Zhou, Jingjing; Zhu, Li; Zhang, Junwei (Frontiers in Psychology, 2022)
Population mobility has been one of the most basic social characteristics of China's reform and opening up for more than 40 years. As the main labor force in Chinese cities, young migrants have made major contributions toward China’s economic miracle as the country has experienced rapid industrialization and urbanization. However, frequent mobility has caused an imbalanced social mentality in young migrants and often leads to issues with social integration, which has made this group more vulnerable with respect to their health. This study used the 2013 and 2015 Chinese General Social Survey (CGSS) data of 1,007 young migrants to investigate social mentality mediating the linkage between social integration and health among young migrants. Additionally, to examine the moderating role of gender, multi-group structural equation modeling was applied to test whether the pathways in the mediation model were significantly different between young male and female migrants. The results suggested that after controlling for the influence of age, marital status, education, and personal annual income, social integration has a significant impact on the health of young migrants in a positive way; social mentality mediated the effect of social integration on this group’s health; and with respect to gender difference, on the three paths of social integration affecting health, social integration affecting social mentality, and social mentality affecting health, young male migrants were more affected than young female migrants. The findings of this study could help improve gender-specific policies on the health of the floating population and offer important theoretical reference and practical suggestions for future research.